What will you do when you grow up?: the social construction of children’s occupational preferences - Merryn Hutchings (Éducation et Socialisation)
Children’ s occupational preferences can provide insights into the ways in which they learn about adult work in the society in which they live. While in traditional societies occupational knowledge and occupational identity can be seen as developing hand in hand, and children can be seen as legitimate peripheral participants (Lave & Wenger, 1991) in adult work, in industrialised societies children’s opportunities to observe and participate in adult work are limited. This article examines the resources which children in such societies use in constructing ideas about their future occupations, and considers whether these ideas can be seen as occupational identities. Finally, implications for the curriculum are examined.